1998
DOI: 10.1002/hep.510270607
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol crystallization in human gallbladder bile: Relation to gallstone number, bile composition, and apolipoprotein E4 isoform

Abstract: Patients with multiple cholesterol gallstones are at increased risk of recurrence after nonsurgical therapy, possibly because of fast biliary cholesterol crystallization. Serum apolipoprotein E4 (apo E4) is a risk factor for primary cholesterol gallstone formation as well as recurrence. We examined potential effects of stone number and apolipoprotein E genotype on crystallization and on various crystallization-influencing factors in gallbladder biles of 36 cholesterol stone patients (25 multiple stones: 10 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
2
14
2
1
Order By: Relevance
“…Patients with ε4 allele had higher cholesterol content in stones, rapid cholesterol crystallization and shorter median nucleation time in the Finnish population [7] while Bertomeu [9] found significantly higher ε4 allele frequency in Spanish patients with gallstones. But other studies [9,30,31] had contradictory results. There were reports that median nucleation time [9] was similar in patients between the genotypes and that the cholesterol saturation index [30] was lower in patients with ε4 allele.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Patients with ε4 allele had higher cholesterol content in stones, rapid cholesterol crystallization and shorter median nucleation time in the Finnish population [7] while Bertomeu [9] found significantly higher ε4 allele frequency in Spanish patients with gallstones. But other studies [9,30,31] had contradictory results. There were reports that median nucleation time [9] was similar in patients between the genotypes and that the cholesterol saturation index [30] was lower in patients with ε4 allele.…”
Section: Discussionmentioning
confidence: 94%
“…But other studies [9,30,31] had contradictory results. There were reports that median nucleation time [9] was similar in patients between the genotypes and that the cholesterol saturation index [30] was lower in patients with ε4 allele. Our study concluded that there was no significant difference in the frequency of ε4 allele between patients and controls.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have reported that certain polymorphisms of the apolipoprotein (APO) E and B genes and the cholesterol ester transfer protein, all of which are involved in carrying cholesterol in the plasma, were associated with gallstones [53][54][55][56][57][58][59]. APOE polymorphism is the most extensively studied polymorphism in gallstone patients; however, controversial results have been reported concerning the protective role of the ε 4 allele against gallstones [53][54][55][56].…”
Section: Genetic Consideration Of Human Cholesterol Gallstone Formationmentioning
confidence: 99%
“…43 Studies are conflicting about whether bile composition, cholesterol saturation index, or nucleation time are different in patients with apoE4 compared with patients without apoE4. 11,21,44 Only further studies can help clarify this confusing situation. We did not have the statistical power to look at interactions between apoE4 and diet, age, or body mass index.…”
Section: Discussionmentioning
confidence: 99%